A survey of sexual harassment and assault in osteopathic medical schools - Kali Chiriboga; Matthew Zeller; Matthew LaPlante; Chaya Prasad (BMC Medical Education)
Abstract Context Large social movements, including the #Metoo movement, have drawn attention to sexual misconduct in medicine, highlighting the lack of published research surrounding sexual misconduct in medical school. Objective Our study sought to investigate the prevalence of sexual misconduct within medical schools, barriers to reporting, and the impact on students’ education. Methods A cross-sectional survey was distributed to medical students enrolled in 14 osteopathic medical schools during the 2018/19 academic year. Standard descriptive statistics and multiple inferential analyses were used depending on the variable analyzed. Results Roughly one in seven (14.0%) experienced sexual misconduct in medical school (4.7% sexually assaulted, 13.0% sexually harassed). Females experienced sexual misconduct roughly four times more than men (Females, 81.1%, Males 18.9%, p < 0.001). Medical students were the most identified perpetrator of SM (SA 63.0%, SH 47.5%) with preceptors being the second most prevalent (SA 12.3%, SH 21.8%). Respondents did not report 80.4% of sexual misconduct claims to their school, citing negative influence on career, being accused of overreacting, gaining a negative reputation, and fear that no action would be taken as top reasons for not reporting. Conclusions This study revealed that students were the most common perpetrator of sexual misconduct against other students. Most victims chose not to report, and many indicated that these experiences negatively impacted their education. Investigation into the impact of changing our hiring and screening processes, as well as changing required disclosures on applications may create a safer learning environment for students and bring us one step closer to improving medicine’s culture around sexual misconduct.